Depressive symptoms and healthcare utilization in late life: longitudinal evidence from the AgeMooDe study - Buczak-Stec, Elżbieta W.; Löbner, Margrit; Stein, Janine; Stark, Anne; Kaduszkiewicz, Hanna; Werle, Jochen; Heser, Kathrin; Wiese, Birgitt; Weyerer, Siegfried; Wagner, Michael; Scherer, Martin; Riedel-Heller, Steffi Gerlinde; et al. (Frontiers in medicine, 2022)
ObjectiveThe aim of this study was to investigate the longitudinal impact of depressive symptoms on utilization of healthcare in terms of GP visits as well as specialist visits and hospital admission in late life among community-dwelling individuals.MethodsLongitudinal data (baseline and follow-up) were derived from the German multicentre, prospective cohort study “Late-life depression in primary care: needs, health care utilization and costs” study (AgeMooDe). At baseline, n = 1,230 patients aged 75 years and older were recruited from primary care practices. Main outcomes of interest were use of health care services: the number of GP visits, the number of medical specialist visits, and hospital admission. We used the Geriatric Depression Scale (GDS-15) to measure depression. Outcomes were analyzed with multilevel random intercept negative binominal regression and logistic random-effects models.ResultsAt baseline (n = 1,191), mean age was 80.7 (SD 4.6) years, 62.9% were female, and 196 individuals (16.5%) had depression (GDS-15 ≥6). Our longitudinal analyses indicated that older individuals with more depressive symptoms visited their GP more often (IRR=1.03; CI [1.01-1.04], p < 0.001), were visiting medical specialists more frequently (IRR=1.03; CI [1.01-1.04], p < 0.01), and had higher odds of being hospitalized (OR=1.08; CI [1.02-1.13], p < 0.01).ConclusionsBased on this large longitudinal study we showed that, after adjustment for important covariates, older individuals with more depressive symptoms had higher health care utilization over time. They visited their GP and specialists more frequently and they had higher odds of being hospitalized. This may suggest that higher utilization of specialist care and increased likelihood of being hospitalized may be also attributable to unspecific symptoms or symptoms that are elevated through depressive symptoms.